Impact of the Covid-19 pandemic on the relationship between financial performance and the ESG of Brazilian publicly traded companies - Silva, Douglas Laurindo da; Mota, Renato Henrique Gurgel; Moura, Angelica Maria Constantino de (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: To analyze the impact of the Covid-19 Pandemic on the relationship between ESG (Environmental, Social and Governance) scores and the financial performance of Brazilian publicly traded companies. Methodology: The sample of this study consists of 100 Brazilian non-financial companies listed on B3 (Brasil, Bolsa, Balcão) with information about ESG. The data collection spanned a time series from 2018 to 2021. ESG scores were collected from the Refinitiv Eikon® database, using ROA (Return on Assets) as a proxy for financial performance. Two research hypotheses were tested: the first regarding the association between ESG and financial performance, and the second examining the effect of Covid-19 on this relationship. The hypotheses were tested using the Ordinary Least Squares (OLS) regression model, with controls for time and sector. Results: The results show that the financial performance of firms with ESG Score, Combined, and Environmental classifications demonstrated a positive and significant relationship, meaning that firms with higher ESG scores offered better financial performance on average. However, the non-significant result for the relationship between financial performance and ESG during the Covid-19 period indicates that it cannot be said whether firms with higher ESG scores were more or less impacted by this pandemic period. Contributions of the Study: This study utilized three types of ESG scores (Score, Combined, and Controversies), as well as the ESG pillars: Social, Governance, and Environmental. This allowed for a more comprehensive examination of the ESG indicators available to investors in the selection of companies for resource allocation. This joint analysis also contributes to the advancement of recent literature by analyzing all available ESG indicators for publicly traded companies in Brazil.